REPRODUCTIVE HEALTH EDUCATION VIDEO INNOVATION AS AN EFFORT TO PREVENT VENEREAL DISEASE AT SMK NEGERI 1 SIMANINDO, SAMOSIR REGENCY - Sihombing, Eka Saudur Renaldi; Pakpahan, Romauli; Purba, Yeni Trisna; Mawaddah, Vanny Chainur; Devi, Icha Sri (LPPM Univ. Ibn Khaldun Bogor, 2024)
SMK Negeri 1 Simanindo, Samosir Regency is in the Tuktuk Siadong tourist area, Samosir Regency. SMK Negeri 1 Simanindo is in an area with a high prevalence of teenagers, reaching 24% of the total population who still lack knowledge about reproductive health. Venereal Disease is a venereal disease resulting from disruption of reproductive health problems. The community service activities are carried out through outreach activities regarding Reproductive Health Educational Video Innovation as an Effort to Prevent Venereal Disease at SMK Negeri 1 Simanindo, Samosir Regency. The aim of the activity is to increase students' knowledge about reproductive health through showing videos whose information is obtained from various sources. The number of students who took part in the activity was 28 students. The first activity was carried out through a pre-test for students to find out their understanding of reproductive health, then provided material and ended with a post-test in the form of games. In conclusion, the activity went smoothly, students gained new knowledge and were highly enthusiastic in participating in the activity. Suggestions for community service activities for teenagers to be further enhanced with increasingly developing media innovations.